Internalization of Multicultural Islamic Education Values In High School Students - Azizah Hanum OK; Mohammad Al-Farabi; Feri Firmansyah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to analyze the Hinai Sub-District Junior High School program in internalizing the values of multicultural Islamic education, to analyze the application of Hinai Sub-District Middle School activities in internalizing the values of multicultural Islamic education, and to analyze the obstacles and supporters in internalizing the values of multicultural Islamic education in Middle Schools throughout the Sub-District. humiliate. This study uses a qualitative research method with a phenomenological approach. The sources of information for this research were Islamic and Christian religious education teachers, civics teachers, school principals, and students. Data collection techniques were collected through interviews, observation, and document studies. Data analysis techniques were carried out using data collection, data reduction, data presentation, and inference. The findings in this study indicate that there are school programs that internalize the values of multicultural Islamic education, including learning process programs, extracurricular programs, school environments, and school rules and regulations. Internalization of the values of multicultural Islamic education is applied in various activities in schools such as teacher activities in teaching, habituation activities, exemplary teachers, activities to read the Koran and pray before learning, prayer, infaq, Ramadan activities, the celebration of Islamic holidays, and mutual cooperation and social service activities.